(untitled) (The Research of Medical Science Review, 2024)
The objective of this study was to determine the frequency of adequate knowledge and positive attitude towards obesity and bariatric surgery among health care staff of Pakistan. This cross sectional study was conducted at Islamabad Medical Complex, Islamabad, over duration of 6 months, from January 2022 to July 2022. For this study a total of 115 health care staff participated through non- probability consecutive sampling. A self-administered questionnaire was designed to determine the frequency of adequate knowledge and positive attitude of healthcare staff towards obesity and bariatric surgery. The primary outcome was to find the frequency and percentage of adequate knowledge and positive attitude of health care staff towards obesity and bariatric surgery. A total of 115 questionnaires were received from health care staff. Generally, a high knowledge (90.43%) of obesity was recorded. However, the overall knowledge regarding bariatric surgery was relatively low (53.04%). Attitude of health care staff towards obesity management was good (60.87%) while their attitude towards bariatric surgery was not appreciable (28.70%). Health care staff has adequate knowledge of obesity and has positive attitude towards obesity management, however, their knowledge about bariatric surgery was relatively low and there was lack of positive attitude towards bariatric surgery.